REASONS FOR A SEMIOTIC APPROACH TO MATHEMATICS EDUCATION - Michael Friedrich Otte; Geslane Figueiredo da Silva Santana; Luciene de Paula; Luiz Luiz Gonzaga Xavier de Barros (Revista Prática Docente, 2019)
Only recently has the semiotic approach become more acceptable or common in mathematics education research and analysis and has gradually disconcerted the Platonic foundation of mathematical objects. In fact it has become increasingly evident that the meanings of concepts develop in the social relationships. The objective is to present the reasons for the use of the semiotic approach in mathematical education. We are arguing, in fact, that the crystallization of mathematical concepts limits creativity and distances school learning from the day to day practices. In theoretical research, questions are addressed such as What is the x in this equation?, evidencing a part of the work of Frege and Benacerraf, with more appreciation to the Peirce’s Semiotic. Illustrative and important examples of such a perspective are presented. For example, the complementarity between text and diagram offers opportunities of critical reflections about the expected results of education in mathematics. Therefore, to think semiotically is to recognize that all knowledge is dynamic, despite being constructed through signs, implying responsibilities, either in choosing the strategy defined for each problem situation, or in identifying the meanings according to the given references and the interactions with the world.